Sustainability, stakeholder governance, and corporate social responsibility - Dorobantu, Sinziana; Aguilera, Ruth V.; Luo, Jiao; Milliken, Frances J. (Advances in strategic management ;, 2018)
The chapters in this volume cover a wide range of theoretical perspectives grounded in strategy, economics and sociology, employ various methodological approaches, and offer new arguments on the connections that exist between firms' decisions relating to sustainability, CSR, and the governance of their stakeholder relations.